¿Es posible un modelo egológico de enseñanza del Derecho? - Luna, Diego (2013)
We start from the experience in teaching the egological theory of law, to further investigate and ask about the possibility of shaping the characters of an egological model of legal education. We take as reference the theoretical models identified by Cardinaux and Clérico: "systematic", "legal realism" and "critical analysis" under the assumption that the epistemological starting point about what is meant by law, and its beliefs have a direct impact on the teaching model assumed, as well as guiding the didactic decisions to be taken in teaching. If it be conceivable an "egological model", at least from a theoretical point of view, to the extent that egology understands the law, as an object of knowledge, as shared human behavior, plural, observed from a specific normative perspective , it would share traits common to all three models of teaching characterized as "systematic", which corresponds to the traditional ius positivism that has its central interest on the norms; "realistic", who concerns about the explanation of social phenomena and predicting the behavior of the judges, and the "critic", which focuses on identifying the relationships among power, ideology and law. We do not intend to arrive at a closed model, but to submit our ideas to discussion as a reflection on the teaching practice.